The RSS :roadmaps for the 21st century - Sunil Ambekar (Rupa, 2019)
The Rashtriya Swayamsevak Sangh (RSS) continues to make headlines, despite several books tracing its journey. Curiosity about the functioning of the RSS has increased phenomenally as swayamsevaks have risen to top positions in government and the Sangh's core ideas of Hindu Rashtra and Ekatmata have become the mainstream lexicon of our social and political space.